KETERKAITAN GENDER, USIA, PENGALAMAN, PENDIDIKAN, TERHADAP ORIENTASI STRATEGI PADA PUSAT PERDAGANGAN GADGET SINGOSAREN, SGM, PARAGON, SOLO SQUARE, PGS DI SURAKARTA - Yusup Hari Subagya; Lucia Desi Kusrini (STIE St. Pignatelli Surakarta, 2018)
Food is a necessity for the people of Indonesia is no exception Surakarta society. The growth of the quantity of food industry in Surakarta very high but growth is very low quality. Competition among the industry is very tight so it requires a strategy that can win the competition.The purpose of this study to analyze the effect of food on the characteristics of SMEs entrepreneurial orientation, customers, competitors, innovation, competitive advantage. This influence can be used to optimize the performance of the organization. This study population food industry in Surakarta. With convenience sampling method determined 100 samples. Methods of analysis used cross-analysis (Cros Tab). The results of this research are gender, education, experience, and age orietasi significant positive effect on customers, competitors, Entrepreneurship, innovation. and performance of SMEs